Online Gaming, Impulsiveness, Aggression and Academic Performance among University Students - Bilal, Ahmed; Iqra Durez; Humera Hameed (Journal of Peace, Development and Communication, 2023)
The current study was aimed to find out that how online gaming affect the student’s impulsiveness, aggression and academic performance for that purpose Game Addiction Scale for Adolescents Lemmens & Valkenburg (2009), The Plutchik Impulsiveness Scale Plutchik & Praag (1989) and Buss-Perry Short- Form Aggression Questionnaire Smith & Bryant (2001) was used to measure the effect between variables. The quantitative method was used for current study. The study was carried out on 250 students by using purposive sampling strategy. The results of Pearson product moment correlation showed that online gaming was found to have strong positive correlation with impulsiveness also Pearson product moment correlation revealed that age was found to have negative significant relationship with gender, semester GPA and CGPA. Gender was found to have positive significant relationship with semester GPA and CGPA. The results of hierarchical multiple regression analysis showed that online gaming only have a strong influence on student’s impulsiveness it has no effect on aggression or academic performance.